2013
DOI: 10.1371/journal.pone.0064047
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Meat Quality Traits in a White Duroc×Erhualian F2 Intercross and Chinese Sutai Pigs

Abstract: Thousands of QTLs for meat quality traits have been identified by linkage mapping studies, but most of them lack precise position or replication between populations, which hinder their application in pig breeding programs. To localize QTLs for meat quality traits to precise genomic regions, we performed a genome-wide association (GWA) study using the Illumina PorcineSNP60K Beadchip in two swine populations: 434 Sutai pigs and 933 F2 pigs from a White Duroc×Erhualian intercross. Meat quality traits, including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 63 publications
5
68
2
Order By: Relevance
“…Indeed, both IM fat and collagen accumulation is lower while muscle mass is higher in the largest compared with the smallest littermates of pigs, indicating the shifting of myogenesis to fibro/adipogenesis in the smallest piglets. 92,93 Consistently, previous studies demonstrated both IM accumulation and fibrosis in fetal and offspring sheep due to maternal over-nutrition, which correlates with downregulated myogenesis [94][95][96] and suggests that IM adipogenesis and fibrogenesis are correlated due to a common cell lineage. Predictably, in genetically high marbling Wagyu cattle, both IM adipogenesis and collagen accumulation are higher than in relatively low marbling Angus cattle.…”
Section: Intramuscular Adipogenesissupporting
confidence: 77%
“…Indeed, both IM fat and collagen accumulation is lower while muscle mass is higher in the largest compared with the smallest littermates of pigs, indicating the shifting of myogenesis to fibro/adipogenesis in the smallest piglets. 92,93 Consistently, previous studies demonstrated both IM accumulation and fibrosis in fetal and offspring sheep due to maternal over-nutrition, which correlates with downregulated myogenesis [94][95][96] and suggests that IM adipogenesis and fibrogenesis are correlated due to a common cell lineage. Predictably, in genetically high marbling Wagyu cattle, both IM adipogenesis and collagen accumulation are higher than in relatively low marbling Angus cattle.…”
Section: Intramuscular Adipogenesissupporting
confidence: 77%
“…For instance, when we compared our a*, b* and pH 24 data with those described in six additional GWAS studies4629303132 we only found one positional coincidence between the SSC10 (70.6 Mb) genomic region associated with LD a* in the Lipgen population (Table 3) and the SSC10 (72.8 Mb) region identified by Ma et al 4. as associated with the same trait in the semimembranosus muscle of White Duroc × Erhualian F 2 pigs.…”
Section: Resultsmentioning
confidence: 64%
“…The genetic determinism of electrical conductivity, acidity and color, which have been often used as predictors of meat quality, has been explored by performing genome-wide association studies (GWAS) in F 2 populations234 as well as in purebred pigs56. An important limitation of using F 2 intercrosses in GWAS studies is that they are not representative of the purebred populations that constitute the selection nuclei of breeding companies.…”
mentioning
confidence: 99%
“…Other studies have reported the relevance of this same chromosomal region. Among these, STRATZ et al (2012) andMA et al (2013) stands out, who also used F2 populations involving commercial lines and identified QTL for pH 45 at positions of 79.5 and 88.26Mbp, respectively, and PONSUKSILI et al (2010), which reported QTL for pH u at 82Mbps using different populations derived from the Duroc breed.…”
Section: Discussionmentioning
confidence: 99%